2018
DOI: 10.1536/ihj.16-630
|View full text |Cite
|
Sign up to set email alerts
|

Early Extubation in the Operating Room after Congenital Open-Heart Surgery

Abstract: SummaryEarly extubation in the operating room after congenital open-heart surgery is feasible, but extubation in the intensive care unit after the operation remains common practice at many institutions. The purpose of this study was to evaluate retrospectively the adequacy of our early-extubation strategy and exclusion criteria through analysis based on the Risk Adjustment in Congenital Heart Surgery method (RACHS-1).This retrospective analysis included 359 cases requiring cardiopulmonary bypass (male, 195; fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…There are many predictors of successful early extubation, which includes preoperative factors such as age at operation, and intraoperative variables, especially the surgical procedure complexity. 2730 Our results were consistent with previous studies. Redlin et al 31 reported a negative association on miniaturized CPB circuits with the time of ventilation in their study of low-priming-volume CPB in neonates with transposition of the great arteries.…”
Section: Discussionsupporting
confidence: 93%
“…There are many predictors of successful early extubation, which includes preoperative factors such as age at operation, and intraoperative variables, especially the surgical procedure complexity. 2730 Our results were consistent with previous studies. Redlin et al 31 reported a negative association on miniaturized CPB circuits with the time of ventilation in their study of low-priming-volume CPB in neonates with transposition of the great arteries.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, early extubation of those patients would have to be carefully evaluated. In CPB, the classical parameters of early extubation have been surgical times, surgical difficulty and patients’ severity measured through risk scores such as PRISM III [4145]. In our study, both parameters were higher in patients who required MV at admission than in those who did not.…”
Section: Discussionmentioning
confidence: 45%
“…In our practice, we try to extubate as soon as possible after Fontan operations, which is a feasible option, unless there is a risk of airway trouble. 12) Clinical implications of the influence of PAI on persistent pleural effusions: After Fontan operations, IVC flow is added to the bidirectional Glenn pulmonary circulation, and pulmonary blood flow (Qp) increases significantly. We speculate that if the pulmonary vascular bed (represented by PAI and pulmonary vascular compliance (Cp)) is not abundant enough to accommodate the added flow, then the "overflowed" Qp would emerge as a persistent pleural effusion.…”
Section: Discussionmentioning
confidence: 99%